Reading Interests and Habits of Indigenous First-Generation College Students: A Phenomenological Study - Punga, Aston Kellyn; Maleng, Getroida; Adoe, Chintamy; Thoomaszen, Friandry Windisany (Psympathic : Jurnal Ilmiah Psikologi, 2025)
The study aims to describe the reading interests and habits of IFGCS and explore the context that impacts them. The research methodology was a descriptive phenomenology study. Data was collected through observation and in-depth interviews. Five participants qualified for collecting the data. Thematic analysis was applied and identified six primary themes and sixteen associated sub-themes as the finding. The main themes included the internal and external factors affecting reading activities, the preferred and least preferred types of books, the internal and external barriers influencing reading, the limited literacy support in the school and community of Timorese students, and economic and cultural challenges in reading within families. The implications of this research suggest recommendations that can be used by students, lecturers, higher education institutions, families, schools, communities, and local governments as microsystems, mesosystems, ecosystems, and macrosystems to foster reading interests and habits.